Determine the External Debt Threshold of the Southeast Asian Countries: Analysis Using Laffer Curve - Van, Thien Hao; Hoang, Van Cuong (Economy of Regions, 2018)
This paper research the relationship between external debt and economic growth. Using the debt Laffer curve theory, the authors determine the maximum debt level of the Southeast Asian countries. Secondary data period 2006-2014 of 10 countries of the Association of Southeast Asian Nations are collected from the Asian Development Bank and the International Monetary Fund website. The authors use the method of regression for balanced panel data with a fixed effect model. The research results indicate that there exists a nonlinear relationship between external debt and economic growth in the Southeast Asian countries, including five variables: budget balance to gross domestic product, the lag of gross domestic product growth, the ratio of total investment to gross domestic product, the ratio of external debt to gross domestic product and the ratio of debt payments on exports of goods and services. These five variables are significant statistics and explain the meaning 24.87 % of the model. The other two: trade openness and trade index are not statistically significant. On the other hand, the research results have found the maximum debt level of the Southeast Asian countries, which is 70.42 %. Based on the study results, the authors suggest some recommendations to help the government of the Southeast Asian countries to build up the maximum debt levels, in line with the socio-economic development goals of their countries in each period.